AUTOMATIC CONTROL OF LIGHTS IN A ROOM USING IOT-BASED PIR SENSOR - Shamasta, Trias Aji; Ayuni, Shazana Dhiya (Journal for Technology and Science, 2025)
Objective: Technological innovations facilitate digital operation, exemplified by smarthome technology. This study aims to implement this technology in a prototype for light control using a PIR sensor. Method: The research adopts a research and development approach, conducting tests on the ESP32 microcontroller, PIR sensor, four-channel relay, and Blynk application-controlled lights. Results: Results indicate that the PIR sensor effectively detects objects within a range of 30cm to 1m. The four-channel relay successfully regulates the on/off functionality of the connected lights. Command execution from the Blynk application button exhibits an average delay of 1.1 seconds for light activation via smartphone. Testing of the PIR sensor indicates an effective object detection range of up to 5m, triggering automatic light activation when the user is within this distance. Novelty: Technological innovations facilitate digital operation, exemplified by smarthome technology.